Genetic diversity analysis of the endangered slipper orchid Phragmipedium longifolium in Costa Rica - Muñoz García, Melania Nelly (2010)
Phragmipedium longifolium is an endangered terrestrial orchid. In Costa Rica, these plants are found growing in small and isolated patches, some of them consisting of just four to six individuals. Information about the genetic variability within and among populations is very important for the conservation of this endangered species. A total of 160 samples were collected in six locations and analyzed with amplified fragment length polymorphism technique. The genetic diversity of P. longifolium in Costa Rica (Hw = 0.1711) is high and differentiation among sampled locations is moderate (upt = 0.2013) in comparison with results of studies in some other terrestrial orchid species using the same technique. The percentage of polymorphic loci was, on average, 51.5. The analysis of molecular variance (AMOVA) indicated the main genetic variation was within sampled locations (80%), even though the variation among locations was also significant. In situ conservation is recommended because, in addition to protecting habitat and avoiding fragmentation, mycorrhizal fungi and pollinators are also protected. Close proximity between populations is required to maintain high genetic variability through a gene flow continuum. It is suggested that conservation of patches with higher genetic variability be prioritized as many are located in unprotected areas. A germplasm bank for ex situ conservation has been established in the living collection at Lankester Botanical Garden using the plants collected in this study. Finally, a search for new locations of this species is also suggested.